A kayak training system for force measurement on-water - Sturm, D.; Yousaf, K.; Eriksson, M. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
Kayaking is a very competitive sport and represented in the Olympic context with two disciplines: slalom and flatwater. The main forces that propel the boat are paddle and foot stretcher force (Mann & Kearney, 1980). Anecdotal evidence collected from coaches involved in the research suggests varying theories on the best profile and synchronisation of paddle and foot stretcher force. It should be extremely helpful for athletes, coaches and researchers to measure these forces in real-time on-water with an unobtrusive, wireless sensor system such as is presented here. Thereby athletes are provided the possibility to perform their training with knowledge of performance (KP), which leads to superior training effects compared to knowledge of results (KR) only. The authors have not been able to identify any previous studies examining paddle and foot stretcher forces simultaneously although previous work has suggested doing so (Michael et al. 2009, Petrone et al., 1998).